Alien : 6-film collection [videorecording (Blu-Ray)]. - Scott, Ridley; Skerritt, Tom; Weaver, Sigourney, 1949-; Cartwright, Veronica; Stanton, Harry Dean, 1926-2017; Hurt, John, 1940-2017; Holm, Ian, 1931-2020; Kotto, Yaphet, 1939-2021; Cameron, James, 1954-; Henn, Carrie; Biehn, Michael, 1956-; Reiser, Paul; et al. (Twentieth Century Fox Home Entertainment, 2020)
Alien: The terror begins as the crew of the space-tug Nostromo responds to a distress signal from a desolate planet, only to discover a deadly life form that breeds within human hosts.